Isolation and Identification of Bioactive Secondary Metabolites - Seca, Ana Maria Loureiro da; Trendafilova, Antoaneta (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The health benefits of food, plants, fruits, and seaweeds stem from the biological activities of their constituents-namely, secondary metabolites. The study of secondary metabolites and their potential to treat and/or prevent a number of diseases has become a research topic of growing interest for biologists, pharmacists, and chemists. Notably, in order to propose a compound as a potential new drug with pharmacological effects, the chemical structure of this compound and its biological activity against a given target must be well established. The Special Issue, "Isolation and Identification of Bioactive Secondary Metabolites", considers species beyond their nutritional value and identifies instances of wider and more efficient use, thereby contributing to a more sustainable management of natural resources. The fifteen articles published in this Special Issue reflect the latest research trends, and consider the isolation, identification, and assessment of the beneficial effects of secondary metabolites from both edible and inedible species. Thus, these contributions collectively demonstrate that these compounds, and their plants of origin, should be valued beyond their nutritional benefits.